Arterial embolization of retained kidney remnant following blunt traumatic injury: A case report. (2016) - Pozzi, Natalie; Koblick, Sarah; Leung, Patricia; Boudourakis, Leon
Highlights: Traumatic urinoma after blunt trauma, nephrectomy and ureter ligation with functional kidney remnant. Arterial embolization for minimally-invasive management of persistent urinoma. Successful resolution of urinoma with minimal adverse effects precluding need for open surgery. Abstract: Introduction: There has been a recent trend toward nonoperative management of solid organ injuries with arteriography and embolization as alternatives to surgical exploration. We examine the use of arterial embolization in the management of a post-subtotal nephrectomy urinoma in a patient with severe renal injury secondary to blunt trauma. Methods: This case report has been reported in line with the CARE criteria [13]. Presentation of case: A 35-year-old female patient presented with a persistent urinoma after an incomplete nephrectomy for blunt renal trauma. Computed tomography scan of the abdomen demonstrated a 47 × 68 × 101 mm 3 collection superior to the remnant of the resected right kidney. With persistence of the urinoma after placement of an 8 French drainage catheter, the patient was taken for arterial embolization of the lower renal artery for ablation of the kidney remnant. Discussion: Most kidney injuries with urinoma formation are treated successfully with supportive measures, however refractory cases require intervention. Arterial embolization has been used successfully in the treatment of traumatic pseudoaneurysms, arteriovenous fistulas, and some renal tumors. In this patient, we extended the use of embolization to infarct vessels of the functioning kidney remnant as an alternative to surgery. Post-embolization the patient recovered well with permanent resolution of the urinoma and short-term side effects limited to short-lived fever and lumbar pain. Conclusion: Arterial embolization should be considered as an alternative to surgery in cases of persistent urinoma following renal trauma with retained remnants.